Gambaran Performed Treatment Index (PTI) pada Mahasiswa Profesi PSPDG di RSGM Universitas Sam Ratulangi - Dinar A. Wicaksono; Johanna A. Khoman; Ribka Kumolontang (Universitas Sam Ratulangi, 2024)
Abstract: Dental filling is a treatment to repair tooth decay to restore its previous shape and function. The indicator of the success of fixed tooth filling is by comparing the number of caries fixed teeth that have been filled with caries experience (DMF-T). Performed treatment index (PTI) is an index that shows the percentage of the number of fixed teeth that have been filled against DMF-T. This PTI describes the motivation of a person to fill cavities to maintain permanent teeth. This study aimed to determine the description of PTI in PSPDG professional students at RSGM Universitas Sam Ratulangi. This was a descriptive study using a cross-sectional research design. Samples were selected using purposive sampling method as many as 71 respondents. The research instruments used were documentation and questionnaires. Data were processed descriptively and then presented in the form of frequency distribution in tabular form. The results showed that PTI in professional students was in the good category (44%) and in the bad category (56%). In conclusion, there were more professional students who pay less attention to their oral health, namely to maintain permanent teeth with caries by carrying out fillings. Keywords: performed treatment index (PTI); Decayed, Missing, and Filled Teeth (DMF-T); professional dentistry students Abstrak: Penumpatan yaitu suatu tindakan perawatan untuk memperbaiki kerusakan gigi agar bisa kembali pada bentuk semula dan berfungsi dengan baik. Indikator keberhasilan penumpatan gigi permanen ialah dengan membandingkan jumlah gigi permanen karies yang telah ditumpat dengan pengalaman karies (DMF-T). Performed treatment index (PTI) adalah indeks yang menunjukkan persentase jumlah gigi permanen yang telah dilakukan penumpatan terhadap DMF-T. PTI menggambarkan motivasi seseorang untuk menumpat gigi berlubang dalam upaya mempertahankan gigi permanen. Penelitian ini bertujuan untuk mengetahui gambaran PTI pada mahasiswa profesi PSPDG di RSGM Unsrat. Jenis penelitian ialah deskriptif dengan desain potong lintang. Sampel penelitian dipilih dengan metode purposive sampling sebanyak 71 responden. Instrumen penelitian yang digunakan yaitu dokumentasi dan kuesioner. Data diolah secara deskriptif kemudian disajikan dalam bentuk distribusi frekuensi dalam bentuk tabel. Hasil penelitian menunjukkan PTI pada mahasiswa profesi dengan kategori baik sebanyak 44% dan kategori buruk sebanyak 56%. Simpulan penelitian ini ialah saat ini masih lebih banyak mahasiswa profesi yang kurang memperhatikan kesehatan gigi dan mulutnya dalam upaya mempertahankan gigi permanen yang mengalami karies dengan melakukan penumpatan. Kata kunci: performed treatment index (PTI); Decayed, Missing, and Filled Teeth (DMF-T)); mahasiswa profesi kedokteran gigi